Gardening in tension-filled rows: an autobiographical narrative inquiry of gardening on the margins. Issue 4 (1st October 2016) - Dubnewick, Michael J.
ABSTRACT: Through the metaphor 'gardening in tension-filled rows' this article unpacks how an inner city Edmonton community garden (Circle), as narrated by the author, was experienced as always in tension to the complex and multivariate stories of gardening and leisure that surrounded him. The use of autobiographical narrative inquiry and poetic form offers the author a vantage for critical self-reflection of his participation at a community garden in a predominantly urban Aboriginal community. Using Lefebvre's spatial triad developed in his book T he production of space, I highlight how I shaped, and was shaped by, the relations I ventured into as a researcher-practitioner, and person at Circle community garden. This article asks the audience to rethink how leisure research/practice ventures into communities and alongside people to question how leisure programming and research resonates with the people and communities involved.